The role of serotonin (5-HT) in behavioral control: findings from animal research and clinical implications - Sánchez, Cristina L.; Biskup, Caroline Sarah; Herpertz, Sabine; Gaber, Tilman Jakob; Kuhn, Cynthia M.; Hood, S. H.; Zepf, Florian Daniel (The international journal of neuropsychopharmacology, 2015)
Abstract. The neurotransmitters serotonin and dopamine both have a critical role in the underlying neurobiology of different behaviors. With focus on the inter
Gesehen am 10.06.2020